Studies on the morphology and mapping of human chromosomes. - Bobrow, M. (My University, 1978)
The published works submitted in this thesis fall into three groups, covering different aspects of the study of the morphology and structure of human chromosomes. Session 1: Studies on chromosome banding and structural polymorphisms of human chromosomes. Session 2: Human gene mapping Session 3: Miscellaneous
Submitted for the degree of MD, University of Witwatersrand.
Keywords: Chromosomes; Chromosome Mapping; cytology